Evaluation of temporomandibular joint morphology and morphometry in male osteoporotic patients using advanced imaging and biochemical markers: A cross-sectional study: Temporomandibular Joint morphology and morphometry - Mustafa H. Kareem, Shara; N. Muhealdeen, Zana (Cellular and Molecular Biology, 2024)
Osteoporosis is a condition with reduced bone mass and disrupted architecture. Osteoporosis affects the Temporomandibular disorders (TMD) by changing bone density and quality. This study aims to determine the nature and extent of temporomandibular joint (TMJ) involvement in osteoporotic patients by correlating TMJ morphological changes detected by CBCT with systemic bone health indicated by BMD T-scores from DEXA and analyzing BTMs in serum and saliva. This study was a cross-sectional study conducted from May 2021 to December 2022. It involved 50 participants divided into two groups (N=25). One group was healthy male, while the other group had osteoporosis male. Saliva and blood samples were collected, and diagnostic imaging was conducted. The prevalence of various bone changes in the condyle was examined using CBCT. Erosion was found to be the most common, followed by Flattening, Osteophyte, and Subchondral cysts. The study group had significantly higher rates of smooth condyle, erosive lesions, and osteophytes compared to the control group. Pseudocyst decreased on the right side but increased on the left side. Pain on the right side increased more in the study group, and the T score for osteoporosis was higher in the study group. Joint spaces, condyle diameter, and glenoid cavity measurements differed significantly between sick and healthy people, as shown by CBCT (P≤0.001). Only the ALP parameter in the serum showed a significant increase in the study group compared to the control group. Saliva analysis revealed higher levels of calcium, osteocalcin, and ALP in the case group compared to the control group. The results of this study showed that CBCT as a specialized technique in imaging by providing detailed images can be used to evaluate osteoporosis and be used as an accurate diagnostic tool.